COLLABORATIVE GOVERNANCE DALAM PENGAKUAN MASYARAKAT HUKUM ADAT DAN HAK TANAH ULAYAT PERSUKUAN PETOPANG KENEGERIAN KUOK DESA BUKIT MELINTANG KECAMATAN KUOK KABUPATEN KAMPAR TAHUN 2017-2019 - Musliana, Tantri; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Writing a thesis entitled "Collaborative Governance in the Recognition of Customary Law Communities and Ulayat Land Rights of the Petopang Kenegerian tribe in Kuok, Bukit Melintang Village, Kuok District, Kampar Regency, 2017-2019", in Kampar Regency, there are actually many units of customary law communities and customary land in every village, especially in Riau Province. In Kampar itself, the existence of customary law communities in Kampar Regency is better known as Kenegerian, where several countries are supervised by the Caliphate. Talking about the existence of customary law communities and their traditional rights have been guaranteed in the 1945 Constitution, however, so far there has not been a comprehensive recognition of customary law communities and customary land rights and has not yet been optimal. There are supporting factors in waste management itself, namely from external and internal factors. This research was conducted in Bukit Melintang Village, Kuok District, Kampar Regency. The purpose of this research is to describe Collaborative Governance in Recognition of Customary Law Communities and Ulayat Land Rights of Petopang Kenegerian Kuok Village, Bukit Melintang, Kuok District, Kampar Regency, 2017-2019. The theory used is the collaboration of Ansel and Gash. The research method used is descriptive qualitative with interview data collection techniques, literature study and documentation, the types of data used are primary data and secondary data. The final result of this research is using a collaborative theory of the implementation of the recognition determination of customary law communities and customary land rights in Kampar Regency, especially in Bukit Melintang Village. This has not been going well according to the theory used. This is due to several factors, such as lack of stakeholder cooperation and undocumented customary forests as a whole.Keywords: Collaborative Governance, Customary Law Community, Ulayat Land.